Pendidikan Karakter Dan Kemajuan Negara;: Studi Perbandingan Lintas Negara - Sultoni, Achmad (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
Each country develops diverse character education. This paper photographs the development of character education in the country of Indonesia, Malaysia, and the United States. The emergence of character education in those three countries is caused by the moral problems arise. Indonesia putsthe character education together with the school system, whereas in the US and Malaysia, it is positioned as a program or field of study. The principles of character education in those three countries compared have different emphases. But the character values developed in those three countries are the same, which is universal; while the implementation method of character education internalization in Indonesia has the scope, complexity and variations more than methods used in Malaysia and the United States.